2012
DOI: 10.2310/jim.0b013e31824a4d79
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Ductal Adenocarcinoma: A Review of Immunologic Aspects

Abstract: With the continued failures of both early diagnosis and treatment options for pancreatic cancer, it is now time to comprehensively evaluate the role of the immune system on the development and progression of pancreatic cancer. It is important to develop strategies that harness the molecules and cells of the immune system to treat pancreatic cancer. This review will focus primarily on the role of immune cells in the development and progression of pancreatic ductal adenocarcinoma (PDAC). We will evaluate what is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 289 publications
0
33
0
Order By: Relevance
“…It has been reported that PDA typically has few TILs, whereas the lymphocytic populations are predominantly found in the stroma surrounding the tumor mass (33), and recent studies suggest that the T cells in long-term survivors with pancreatic cancer target neoantigens (34). The presence of high numbers of TILs and extensive infiltration are major indicators of favorable patient prognosis and positive therapeutic responses in treating several solid tumors, including colorectal cancer (35), lung cancer (36), and ovarian carcinomas (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PDA typically has few TILs, whereas the lymphocytic populations are predominantly found in the stroma surrounding the tumor mass (33), and recent studies suggest that the T cells in long-term survivors with pancreatic cancer target neoantigens (34). The presence of high numbers of TILs and extensive infiltration are major indicators of favorable patient prognosis and positive therapeutic responses in treating several solid tumors, including colorectal cancer (35), lung cancer (36), and ovarian carcinomas (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Professional antigen presenting cells (APC) such as dendritic cells (DC) and macrophages play a pivotal role in tumorigenesis and in the complex microenvironment of pancreatic cancer and periampullary adenocarcinomas [2]. Tumour associated macrophages (TAM) can roughly be divided into two subtypes, M1 and M2, whereof M1 are associated with pro-inflammatory properties and M2 anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…PDAC develops by an adenoma to carcinoma sequence as a result of accumulating genetic alterations, which provide signals (e.g. TGFβ via SMAD4) that promote recruitment of immune cells [8, 80, 89]. Histologically, microscopic pancreatic intraepithelial neoplasms (PanIN) progress from intraepithelial to invasive pancreatic cancer and parallel the accumulating genetic alterations in the adenoma to carcinoma succession of PDAC [8, 33, 50].…”
Section: Introductionmentioning
confidence: 99%